2021
DOI: 10.1088/1674-1056/abddad
|View full text |Cite
|
Sign up to set email alerts
|

Effects of post-sinter annealing on microstructure and magnetic properties of Nd–Fe–B sintered magnets with Nd–Ga intergranular addition*

Abstract: We investigate the effects of post-sinter annealing on the microstructure and magnetic properties in B-lean Nd–Fe–B sintered magnets with different quantities of Nd–Ga intergranular additions. The magnet with fewer Nd–Ga additions can enhance 0.2 T in coercivity, with its remanences nearly unchanged after annealing. With the further increase of the Nd–Ga addition, the annealing process leads coercivity to increase 0.4 T, accompanied by a slight decrease of remanence. With the Nd–Ga addition further increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…The stability of the multicomponent liquid grain boundary phase is increased, so that most of the diffusion elements are retained in the grain boundary and do not easily enter the main phase, thereby broadening the thin grain boundary in the magnet and increasing its continuity. The thicker and continuous thin grain boundaries can effectively inhibit the magnetic exchange coupling between grains [35,36]. This is why Tb60 diffusion magnets still have higher coercivity than Tb diffusion magnets when only 60% Tb content is contained in the diffusion source.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of the multicomponent liquid grain boundary phase is increased, so that most of the diffusion elements are retained in the grain boundary and do not easily enter the main phase, thereby broadening the thin grain boundary in the magnet and increasing its continuity. The thicker and continuous thin grain boundaries can effectively inhibit the magnetic exchange coupling between grains [35,36]. This is why Tb60 diffusion magnets still have higher coercivity than Tb diffusion magnets when only 60% Tb content is contained in the diffusion source.…”
Section: Resultsmentioning
confidence: 99%
“…in the magnet and increasing its continuity. The thicker and continuous thin grain boundaries can effectively inhibit the magnetic exchange coupling between grains [35,36]. This is why Tb60 diffusion magnets still have higher coercivity than Tb diffusion magnets when only 60% Tb content is contained in the diffusion source.…”
Section: Resultsmentioning
confidence: 99%
“…Exchange decoupling between adjacent grains can be improved by microstructural optimization. [12] Further research found that coercivity enhancement can be influenced by the Al/Cu ratio in the diffusion source. [13] Besides, Al can improve the wettability of the GB phase to enhance the diffusion rate, while replacement of some of the Fe by Al can further improve coercivity, although the anisotropy field of the Nd-Fe-B sintered magnets decreases slightly.…”
Section: Introductionmentioning
confidence: 98%